Management of Academic Supervision by Junior High School Seunagan Rayal District Principals in Competency Development - Hambali, Hambali; Asiah, Nur; Masrihtah, Iis; Sulaiman, Sulaiman; Muttaqin, Reza (LP. Ma'arif Janggan Magetan, 2025)
This study examines the role of school principals in managing academic supervision to improve the competence of junior high school (SMP) teachers in the Seunagan sub-district. Using a qualitative descriptive approach, data were collected through observations, interviews, and document analysis at several schools in Seunagan Rayal district. The results show that academic supervision is carried out regularly based on a planned schedule and includes pre-observation meetings, classroom visits, and follow-up feedback. Supervision focuses on helping teachers improve in areas such as lesson planning, subject knowledge, teaching methods, and classroom management. Thematic analysis showed that teachers improved in five main areas: planning, managing learning, mastering material, using methods effectively, and working with others. About 75% of teachers said they became more confident in teaching, and 68% became more reflective after being supervised. School principals also reported a 60% improvement in teaching quality. The study concludes that supervision, when done consistently and collaboratively, helps teachers grow professionally and supports better learning outcomes in line with national education policies like Merdeka Belajar.